Changes in Body Temperature and Sleepiness after Stimulation with the Aroma of Whiskey: a Preliminary Study - Koda, Hirofumi; Awaji, Yukako; Uchida, Masaaki; Nagai, Narumi (Nihon Eiyō, Shokuryō Gakkai shi, 2018)
This study was conducted to evaluate sleepiness, changes in body temperature and autonomic nervous system activity after stimulation with the aroma of whiskey. The subjects were 12 young female volunteers. At 9:00 a.m. on two different days, the subjects smelled continuously for 65 minutes a cut cotton pad soaked in whiskey (diluted eight-fold) or water (blank) placed inside a mask. Before and after exposure, subjective sensations of sleepiness and awareness, core (eardrum) and peripheral (toe tip) temperatures, and autonomic nerve activity (heart rate variability) were continuously measured. The findings revealed that: 1) the absolute sleepiness score did not differ significantly between the groups, and 2) the core body temperature increased gradually by approximately 0.05℃ over 65 min in the water group; the core body temperature was increased by approximately 0.15℃ at 30 min, then decreased in the whiskey group. 3) Only in the whiskey group, the difference in core body temperature between the peak value and at each time point (30 and 45 min) was significantly correlated with the change in the sleepiness score. These results suggest that stimulation with the aroma of whiskey may affect the core body temperature. To evaluate the effect of whiskey aroma on sleepiness, further study is warranted.